(3JYQja GdaFI HGdCSFdI GdeGFI GdJi SFd YfgG GdSjhWis - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3hHYO aEfi QLd MHH Edi GdYde hGdfXQ ajg hgPg GdGSFdI bO QaYJ Edi hgj eMJGLI Edi aVd fXQ hSYI GWdGY aCLHJ YfgG s
(3BNQgG (B:s
(3hYde JYHjQ QDjG Gdfhe eYJHQ dg GUhd HecJhH heSfhf hef jYGfjg dG EKe Ydjg GPG QGYi GdbhGYO ajg ZjQ eaJhf Ke GdLhGH HgPG Yf eSGFdg aGdMeO ddg MeOkG ZjQ eefhf s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B535s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B421s
Keywords: (3GdeYGQa GdYGeIs